Meta-Analysis: The Effect of E-Module Learning Media on Biology Materials on Learning Outcomes of High School Student - Amelia Kartika; Fita Kharisma Ameliyah; Glorio Brian; Rani Dwi Lintang; Zahra Syarifah; Rusdi Rusdi; Dini Safitria (International Journal of Learning Media on Natural Science (IJLENS), 2025)
This research investigates the effectiveness of e-module learning media on high school students’ biology learning outcomes through a comprehensive meta-analytic approach. By synthesizing data from 20 selected empirical studies, the study employed Cohen’s d to calculate effect sizes and assess the extent of the e-modules' impact on students' academic performance. The analysis revealed that most studies reported large to very large effect sizes, with values reaching up to 6.10, indicating a significant positive influence of e-modules on students' cognitive achievement. Moreover, various types of e-modules—such as those based on scientific literacy, POEI (Predict-Observe-Explain-Interpret), problem-based learning, and COVID-19 contextualized content—were shown to enhance independent learning, critical thinking, and adaptability within digital learning environments. The findings suggest that e-modules represent a promising and impactful innovation for 21st-century biology education, offering substantial potential to support student-centered and technology-integrated instructional practices.